STRATEGI PENINGKATAN KUALITAS PELAYANAN DALAM KERAGAMAN KARAKTER TAMU - Vanessa Emmanuela Sitanggang; Jonathan Polin Silalahi; Rafli Ihza Mahendra; Rabbani Aidil Rizqi (JURNAL BISNIS HOSPITALITI, 2026)
This study aims to analyze the service quality at Niagara Hotel Parapat and to formulate strategies to improve service quality in response to the diverse characteristics of hotel guests. A quantitative approach was employed using the Importance Performance Analysis (IPA) and Gap Analysis methods. The findings indicate that the overall service quality at Niagara Hotel Parapat is considered good; however, several service attributes have not fully met guests' expectations. The level of conformity analysis shows that most service attributes achieved high conformity scores, while attribute A10 recorded the lowest conformity level at 71.09%. Furthermore, Gap Analysis revealed an average gap score of -0.26, indicating that the hotel's service performance remains slightly below guest expectations. The largest negative gap was identified in attribute A10, with a score of -1.22. Based on these findings, the recommended improvement strategies include enhancing staff communication skills, responsiveness, complaint-handling abilities, and emotional control when serving guests with diverse characteristics. In addition, periodic service evaluations should be conducted to ensure continuous service quality improvement, thereby increasing guest satisfaction and strengthening the hotel's competitiveness.